Investigation of the bee-repellent properties of cotton fabrics treated with microencapsulated essential oils. Issue 8 (April 2019) - Eyupoglu, Seyda; Kut, Dilek; Girisgin, Ahmet Onur; Eyupoglu, Can; Ozuicli, Mehmet; Dayioglu, Habip; Civan, Mustafa; Aydin, Levent
In this study, to produce single-use bee-repellent fabrics, a variety of essential oils were encapsulated with gum arabic wall material at a 1:5 ratio of wall to the core substance. The following core substances were used: lavender oil, laurel oil, fennel oil, N, N-diethyl-3-methylbenzamide (DEET), lavender + laurel oil, lavender + fennel oil, laurel + fennel oil, lavender + fennel + laurel oil, lavender oil + DEET, fennel oil + DEET and laurel oil + DEET. Lavender, fennel and laurel oils were analyzed by high-performance liquid chromatography. In this context, 11 different microcapsules were produced. After the microencapsulation process, the microcapsules were analyzed with a light microscope and by Fourier transform infrared spectroscopy. Furthermore, an image processing application was developed and implemented to determine the particle size distribution of the microcapsules. After the analysis of the microcapsules, cotton fabric samples were treated with the microcapsules. In order to analyze the microcapsules on the fabric samples, scanning electron microscopy (SEM) was used. To analyze the bee-repellent abilities of the fabric samples, 12 different measurement cabinets made of pine tree and glass were produced. According to the results, lavender and fennel oils can be used as bee-repellent alternatives to DEET in beekeeping.